2018
DOI: 10.1108/oir-09-2016-0290
|View full text |Cite
|
Sign up to set email alerts
|

Peer-to-peer word-of-mouth: word-of-mouth extended to group online exchange

Abstract: Purpose The purpose of this paper is to investigate how peer-to-peer word-of-mouth (PPWOM) conversations evolve over time because of the dynamic social nature of the community in which they take place. Design/methodology/approach This study analyzed PPWOM conversations in an online community website for new and expectant mothers. Two data collection phases were undertaken during a four-year period. In phase I, messages were collected for a one-month period from five different bulletin boards (i.e. cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Similarly, Liao et al (2016) observed that CS does have a significant influence on RI for a range of services. Importantly, one cannot deny the fact that CS is indeed an essential element to any service, being a strong predictor of RI and WOM (Saleem et al, 2017;Toder-Alon and Brunel, 2018). Thus, we hypothesize:…”
Section: Service Quality Customer Satisfaction and Customer Loyaltymentioning
confidence: 91%
“…Similarly, Liao et al (2016) observed that CS does have a significant influence on RI for a range of services. Importantly, one cannot deny the fact that CS is indeed an essential element to any service, being a strong predictor of RI and WOM (Saleem et al, 2017;Toder-Alon and Brunel, 2018). Thus, we hypothesize:…”
Section: Service Quality Customer Satisfaction and Customer Loyaltymentioning
confidence: 91%
“…Reviews can also be seen as a type of contribution to UGC; hence, we use image motivation theory to explain why social image can stimulate contribution efforts, and why increasing reviewer follower can enhance image motivation. Social functions are believed to have an impact on users' attitudes and engagement toward the platform (Gvili and Levy, 2018; Toder-Alon and Brunel, 2018). Chu and Kim (2011) pointed out that sharing useful information will also affect users' online social relationships, and this effect is positively correlated with users' eWOM behaviors.…”
Section: Moderators: Reviewer Characteristicsmentioning
confidence: 99%
“…Prospective students search information from various information sources about institution choice factors such as academic reputation, location proximity, financial assistance and learning assistance (Wong et al , 2016; Ng and Galbraith, 2016). As well as searching for information, students also seek advice from social networks such as friends, peers (Toder-Alon and Brunel, 2018), teachers and parents (Chalupová and Borůvková, 2012), providing a new social context. It is crucial that information and advice are adequately available in order to facilitate students’ decision-making process concerning institution choice.…”
Section: Introductionmentioning
confidence: 99%